Evaluation of a real-time PCR assay performance to detect Mycobacterium tuberculosis, rifampicin, and isoniazid resistance in sputum specimens: a multicenter study in two major cities of Indonesia - Parwati, Ida; Chaidir, Lidya; Yunus, Muhammad; Montain, Maya Marinda; Budhiarko, Dini; Selasih, Siti Fatimah; Ristandi, Ryan Bayusantika; Rachman, Rifky Waluyajati; Nurhayati, Raden Desy; Pambudi, Imran; Budiyati, Akterono Dwi (Frontiers in Microbiology, 2024)
Background: Tuberculosis (TB) is one of major global health issues due to its high mortality rate especially in low and middle-income countries. One of the key success points for TB eradication program is early TB diagnosis which require rapid and accurate diagnostic testing. This study aimed to evaluate the performance of a newly developed RT-PCR kit (Indigen MTB/DR-TB RT-PCR) in routine TB clinical setting. Method: A multi-fluorescence RT-PCR assay was designed and developed to detect region within IS6110, rpoB, katG, and inhA of Mycobacterium tuberculosis (MTB) genes. Sputum specimens were obtained from suspected TB patients who visited TB health care facilities in two major cities of Indonesia from September 2022 to May 2023. Specimens were assessed using Indigen MTB/DR-TB RT-PCR, acid fast bacillus (AFB) smear microscopy, MTB culture, and drug susceptibility testing (DST) methods.2 ) was used to analyze the Indigen performance relatively to culture methods. Result: Performance of Indigen MTB/DR-TB RT-PCR to detect MTB was assessed using 610 sputum specimens obtained from suspected patients. The overall sensitivity and specificity were 94.12% (95% CI: 90.86%-96.48%) and 98.32% (95% CI: 96.20%-99.46%), respectively. When the analysis was performed on AFB-smear negative tuberculosis subjects (386 subjects), lower sensitivity level was found at 78.57% (95% CI: 68.26%-86.78%) whilst the specificity remained similar at 98.34% (95% CI: 96.18%-99.46%). The overall performance of Indigen MTB/DR-TB RT-PCR to detect MTB showed substantial agreement with MTB culture method (Kappa value 0.93). In comparison to DST, the sensitivity and specificity level of Indigen to detect RIF-resistance or INH-resistance were 78.2% (95% CI: 61.8%-90.2%) and 82.8% (95% CI: 64.2%-94.2%), respectively, whilst the specificity level for both groups were at 100% (95% CI: 87.7%-100%). Conclusion: Indigen MTB/DR-TB RT-PCR demonstrated a reliable performance for TB molecular diagnostic testing and can be implemented in routine TB diagnostic setting.